Exfoliative Vaginal Cytology: An Effective Tool To Know The Reproductive Status Of The Bitch - Gupta, A.K.; Dhami , A.J.; Ghodasra , D.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The exfoliative vaginal cytology was recorded in an attempt to identify the reproductive status/stage of oestrous cycle in 30 bitches. Deep vaginal smears were collected by cotton swab technique from adult bitches in proestrus (n=6), oestrus (n=6), dioestrus/ metoestrus (n=6), anoestrus (n=6) and pregnancy (n=6) and were examined using Giemsa stain. The differential count of exfoliated vaginal epithelial cells showed that the mean percentages of superficial, intermediate and parabasal cells were 65.33 ± 2.38, 25.17 ± 1.96 and 9.50 ± 0.67 in proestrus, 95.33 ± 0.67, 4.33 ± 0.62 and 0.33 ± 0.21 in oestrus, 18.33 ± 0.88, 29.33 ± 1.28 and 52.33 ± 0.72 in dioestrus, 12.33 ± 0.88, 28.50 ± 1.34 and 59.17 ± 0.95 in anoestrus and 20.50 ± 1.18, 56.83 ± 3.19 and 22.67 ± 2.60 in pregnant bitches, respectively. Vaginal smears were characterized by presence of massive erythrocytes in proestrus, clear background of smear in oestrus, heavy infiltration of polymorphonuclear cells in dioestrus, very few cells mostly parabasal in anoestrus and dirty background in pregnant bitches. It is thus concluded that vaginal cytology can be conveniently used to evaluate the reproductive stages in bitches.
Keywords: Bitches; Exfoliative vaginal cytology; Diagnostic tool; eproductive stages/status